MO624COMBINATION TREATMENT WITH LISINOPRIL AND EMPAGLIFLOZIN IMPROVES BIOCHEMICAL AND HISTOLOGICAL MARKERS OF DIABETIC NEPHROPATHY IN HYPERTENSIVE UNINEPHRECTOMIZED DB/DB MICE. (29th May 2021) - Ostergaard, Mette Viberg; Christensen, Michael; Secher, Thomas; Lercke Skytte, Jacob; Roostalu, Urmas; Gravesen Salinas, Casper; Sembach, Frederikke Emilie; Jelsing, Jacob; Fink, Lisbeth N; Vrang, Niels
Abstract: Background and Aims: Emerging treatments of diabetic kidney disease (DKD) include SGLT2 inhibitors and GLP-1 receptor agonists that are nephroprotective beyond their blood glucose lowering effects. Despite this progress, patients with diabetes are still at risk of developing DKD, and drug discovery remains impeded by the lack of reproducible rodent models exhibiting features of human DKD. To confirm the translatability of an advanced mouse model, we tested standard of care in the setting of type 2 diabetes and hypertension. Method: Female db/db mice were injected with a renin-encoding adeno-associated virus construct (reninAAV) to induce hypertension and uninephrectomized (UNx) at 7-8 weeks of age. At 12 weeks of age, daily dosing with vehicle, lisinopril, empagliflozin, or the combination (combo) was initiated. Blood glucose (BG) was measured every third week, while urine albumin-to-creatinine (ACR) and KIM1 were measured in spot urine samples collected before termination at 24 weeks of age. Cystatin C was measured in terminal plasma, while terminal kidney samples were collected for 3D light sheet microscopy and 2D histology: Glomerulosclerosis scoring was performed by AI-assisted automized scoring, whereby glomeruli were given scores from 0 (normal glomerulus) to 4 (glomerulus with global glomerulosclerosis), and morphometric quantification of kidney collagen 3, CD11b, and KIM1 load was performed. Results: In reninAAV UNx db/db mice, 12 weeks treatment with empagliflozin and combo reduced fed BG (12.3±1.5 and 13.1±0.9 mM, vehicle: 18.0±1.9 mM) and HbA1c (5.5±0.2 and 5.8±0.2%, vehicle: 7.4±0.03%). Treatment with lisinopril and combo reduced urine ACR (8110±1320 and 2508±346 µg/mg, vehicle: 26, 138±1820 µg/mg) and KIM1-to-creatinine (7.5±1.1 and 3.9±0.6 ng/mg, vehicle: 24.8±3.2 ng/mg), while treatment with empagliflozin alone worsened urine ACR (41, 523±4670 µg/mg). Glomerular hypertrophy as assessed by 3D imaging was reduced in reninAAV UNx db/db mice combo treated animals compared to vehicle (glomerular volume: 1.46*10 5 ±4.3*10 3 and 1.65*10 5 ±4.3*10 3 µm 3 ), while treatment with empagliflozin alone worsened glomerular hypertrophy (1.83*10 5 µm 3 ). The total number of glomeruli per kidney was not affected by treatments. Compared to vehicle treatment, lisinopril and combo treatment reduced the fraction of score 3 + 4 glomeruli (% GS 3 + 4 glomeruli: 0.38±0.06 and 0.27±0.03%, vehicle: 0.54±0.05%) Glomerulosclerosis index (GSI) was also reduced by lisinopril and combo treatment (GSI: 2.29±0.10 and 2.04±0.05, vehicle: 2.62±0.09). Treatment with empagliflozin alone worsened GSI (2.95±0.11). Whereas treatments did not significantly affect collagen 3, lisinopril and combo treatment reduced CD11b (total CD11b mass: 0.25±0.03 and 0.24±0.04 mg, vehicle: 0.57±0.07 mg) and KIM1 (total KIM1 mass: 0.25±0.06 and 0.17±0.09 mg, vehicle: 2.01±0.37 mg), whereas empagliflozin did not affect CD11b and KIM1. Conclusion: Responses to the combination treatment with lisinopril and empagliflozin showed improvement of urine and histological markers of DKD. Together, these data confirm the translatability of the ReninAAV UNx db/db mouse model of DKD in type 2 diabetes.